Media Coverage of Pediatric Environmental Health Risks and its Effects on Mothers' Protective Behaviors. Issue 3 (13th August 2015) - Mello, Susan; Hornik, Robert C.
Abstract : This study explores the relationship between exposure to U.S. media coverage of chemical threats to pediatric environmental health and mothers' behaviors to protect their children. Prior content analytic work revealed that media coverage volume from September 2012 to February 2013 differed significantly by type of chemical (i.e., pesticides = high coverage volume ; bisphenol A [BPA] = moderate ; and arsenic = low ). Survey data collected from new and expecting mothers in March 2013 ( n = 822) revealed mothers incidentally encountered—or scanned —this information in the media in the prior six months, and after adjusting for a series of potential confounders, such scanning was positively associated with mothers' self‐reported behaviors to reduce chemical exposures. To test the hypothesis that coverage volume moderates the relationship between scanning and behavior, content analysis and survey data were combined in mixed effects regression analyses. Results showed significant differences between the effects of media scanning at different levels of coverage volume, but in a direction not entirely consistent with the study's hypothesis. The relationship between scanning and behavior was strongest for BPA, suggesting that a characteristic of media coverage other than volume may drive maternal responses to environmental health threats. Implications of these findings for risk communication research and practice are discussed.